DOUBLING THE ELECTIONS: A REIVINDICATION OF FEDERALISM (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
This article will focus on the analysis of one of the most controversial points of the autonomies of the Argentine provinces referred to institutional political autonomy, specifically the possibility of establishing the provinces their own electoral timetable and thus be constituted in what I call ‘the judge of his own choices’. For this, a synthetic analysis of the jurisprudence of our Supreme Court of Justice referred to the control of constitutionality that is carried out on the provincial electoral processes is carried out, presenting the most relevant cases and the most recent ones that reveal, to understand this author, an apparent contradiction with their recognition of the authority of the provinces to become the decision-maker of their electoral processes. The conclusions raise two major questions: what are the principles of the federal system that the provinces must ensure, and whether the Supreme Court of Justice is the custodian of the principles of federal order regardless of the local estates. The response to them will allow us to advance in the recognition of the full autonomy of the provinces that the National Constitution assures them.
Keywords: provincial political autonomy; electoral federalism